PENGARUH LABELISASI HALAL DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN PADA GENERASI Z DI KABUPATEN TULUNGAGUNG - Meiliana Nurnaningtias; Muhammad Aswad (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
Generation Z at this time when buying an item is not just a halal label that is a concern but is more concerned with who is the brand ambassador. This study aims to find the effect of partially or simultaneously halal labeling and brand ambassadors on purchasing decisions for Korean Spicy instant noodles. This research was conducted on Generation Z in Tulungagung Regency. The sample collection in this study used a snowball sampling technique to consumers of Generation Z instant noodles in Tulunggaung Regency. The sampling used was through a questionnaire (questionnaire) which was distributed through the google form. The data analysis technique used is multiple linear regression with the help of the SPSS version 21.0 computer application program. Partially, the data analysis in the study showed that the halal labeling variable had a positive and significant effect on purchasing decisions and partially the brand ambassador variable had a significant positive effect on purchasing decisions. The translation of the coefficient of determination (R2) is 0.667, which means that both halal labeling variables and brand ambassadors simultaneously (simultaneously) contribute 66.7% to purchasing decisions, while 33.3% comes from other factors and not from this study.